2015
DOI: 10.1098/rspb.2014.2321
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of opsin expression in birds driven by sexual selection and habitat

Abstract: Theories of sexual and natural selection predict coevolution of visual perception with conspecific colour and/or the light environment animals occupy. One way to test these theories is to focus on the visual system, which can be achieved by studying the opsin-based visual pigments that mediate vision. Birds vary greatly in colour, but opsin gene coding sequences and associated visual pigment spectral sensitivities are known to be rather invariant across birds. Here, I studied expression of the four cone opsin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 80 publications
3
76
0
1
Order By: Relevance
“…In many systems it has been shown that opsin expression levels match the relative abundance of the different cone types leading to the conclusion that opsin expression reflects changes in relative cone abundances (Hagstrom et al, 1998). However, preliminary data suggest this might not be the case in birds (Bloch, 2015) and data is still not available for enough species, particularly beyond fish, to know whether opsin expression is generally a reflection of relative photoreceptor abundances (Fuller et al, 2004;Fuller and Claricoates, 2011).…”
Section: From Opsin Genes To Spectral Tuningmentioning
confidence: 81%
See 2 more Smart Citations
“…In many systems it has been shown that opsin expression levels match the relative abundance of the different cone types leading to the conclusion that opsin expression reflects changes in relative cone abundances (Hagstrom et al, 1998). However, preliminary data suggest this might not be the case in birds (Bloch, 2015) and data is still not available for enough species, particularly beyond fish, to know whether opsin expression is generally a reflection of relative photoreceptor abundances (Fuller et al, 2004;Fuller and Claricoates, 2011).…”
Section: From Opsin Genes To Spectral Tuningmentioning
confidence: 81%
“…In addition to variation in opsin gene sequence, opsin expression has been shown to vary significantly across species in various systems (Laver and Taylor, 2011;Sandkam et al, 2015), in many cases in a way consistent with variation in the light environment (Fuller et al, 2004;Hofmann et al, 2009;Fuller et al, 2010;Bloch, 2015) or even measures of sexual selection (Bloch, 2015). The immediate consequences of changes in gene expression remain poorly understood.…”
Section: From Opsin Genes To Spectral Tuningmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies in invertebrates and vertebrates have shown a link between colour vision and intraspecific signalling (e.g. [1][2][3][4]), but there has been relatively little work on mammals. In New World monkeys (NWMs), colour vision is highly variable, and a substantial body of research has investigated the ecological and evolutionary basis of this variation [5], which has implications for the acquisition of trichromacy in humans, apes and Old World monkeys (Catarrhini) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, dimorphisms in both song and plumage colors have been shown to be associated with an assortment of life history traits besides mating system, including breeding latitude, seasonal migration, nesting behavior, and territoriality (Martin and Badyaev, 1996;Friedman et al, 2009;Price, 2009;Soler and Moreno, 2012;Johnson et al, 2013;Odom et al, 2015). Nevertheless, the perception that levels of sexual dimorphism reflect levels of sexual selection remains pervasive, even among some researchers (e.g., Seddon et al, 2013;Bloch, 2015).…”
Section: Sexual Dimorphism Is Not Due To Sexual Selection Alonementioning
confidence: 99%